Sulfur hexafluoride - A powerful new atmospheric tracer - Maiss, Manfred; Steele, Paul; Francey, Roger; Fraser, Paul; Langenfelds, Ray; Trivett, Neil; Levin, Ingeborg (1996)
Long-term observations of the atmospheric trace gas sulfur hexafluoride (SF6) at four background monitoring stations, Neumayer, Antarctica (1986-1994), Cape Grim, Tasmania (1978-1994), Izana, Canary Islands (1991-1994) and Alert, Canada (1993-1994) are presented. These data sets are supplemented by two meridional profiles collected over the Atlantic Ocean (1990 and 1993) and occasional observations at the regional site Fraserdale, Canada (1994). The analytical system and the method of SF6 calibration are described. Compared with data from Neumayer and Izana reported earlier, measurements are updated for all sites until the end of 1994 and the precision has improved by more than a factor of 2. With the Cape Grim archived air samples, the atmospheric SF6 chronology is extended by 8 more years back to 1978. For the period from January 1978 to December 1994 the data confirm a stable and unbroken quadratic rise in tropospheric SF6 from 0.50 to 3.11 ppt in the southern hemisphere and for July 1991 to December 1994 from 2.69 to 3.44 ppt in the northern hemisphere. The global mean tropospheric increase rate in late 1994 was 0.225 ppt/yr (6.9%/yr). The long term trend and interhemispheric gradients are due to industrial production and emission, rising approximately linearly with time and located predominantly (94%) in the northern hemisphere. The interhemispheric exchange time (1.7+/-0.2 yr) derived from SF6 ground level observations when using a two-box model of the atmosphere is considerably larger if compared to the exchange time derived from two- and three-dimensional models (1.1 yr). The chemical and biological inertness of SF6 up to stratospheric conditions results in an atmospheric lifetime of more than 800 years and makes SF6 a powerful tool for modelling transport processes in the atmosphere. Moreover, the tropospheric SF6 chronology is a very valuable input function for mixing studies in linked compartments like the stratosphere, the hydrosphere and the cryosphere.